Peningkatan Kapasitas Ibu dan Kader Posyandu Terhadap Sterilisasi Peralatan Bayi melalui Pelatihan Pembuatan Deterjen Bayi - Sitti Usmia; Nurul Hidayah Bohari; Haerani; Arfiani (JCS, 2024)
Health is the most important thing in human life. Regarding this issue, whether or not the tools used in daily activities are sterile plays a very important role, especially the tools that are consumed. The aim of this activity is for mothers and posyandu cadres to optimize themselves in terms of sterilizing baby equipment through training in making baby detergent. This activity was carried out on October 16 2024. In the initial stage, education was provided regarding the sterilization of baby equipment, then continued with a question and answer process. The final stage was a demonstration regarding the process of making baby detergent. The participants were very enthusiastic about community service activities. Especially when making baby detergent. It is hoped that after making baby detergent, the participants can create their own jobs so that the participants can be productive even if they only work at home.